The Political Concept of the Constitution and the Concepts ofHidden Constitution, Modest Constitution and ,, Behind the Scenes" Constitution - Jelena Trajkovska Hristovska (ICARSH-Conference Proceedings, 2019)
The political concept of the constitution is bound with the theory of constitutionalism. The political concept of the constitution, in defining the constitution, starts from its purpose. The supporters of this understanding of the constitution, advocate the thesis that the constitution is the principal act or set of principles that limit the state power. Thus the constitution is only one of the elements of constitutionalism, which provides limited power. As the highest act in the legal system, the constitution institutionalizes and objectifies the exercise of state power, and thus restricts it. Understood in this way, the basic goal of the constitution is to determine and institutionalize means, mechanisms and instruments for limiting and controlling political power. In this paper, the attitude of this understanding of the constitution will be elaborated vs. the notion of a ,,hidden constitution”, a ,,modest constitution”, a ,,constitution in exile” and a ,,behind-the-scenes” constitution as modern views of the constitution. The indicated terms for designating the constitution are in relation to the role of the institutions for control of the constitutionality of legal acts. These authorities realize their role as "the guardian of constitutionality" through the process of interpreting the weak, unclear and modest constitutional provisions. In the process of interpreting unclear constitutional provisions, they often face the temptation to act as a provision-maker. Viewed from this aspect, their actions outside the constitutionally prescribed competencies, and under the veil for the need for control of the constitutionality, is contrary to the request for framing the powers of the state, contrary to the request for action within the constitution and contrary to the idea of limited and controlled power, i.e constitutionalism
Keywords: Constitution, Constitutionalism, Modest constitution”, Behind- the- Scenes Constitution”, Constitutionality.